2018
DOI: 10.7555/jbr.32.20180007
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E in diet-induced obesity: a paradigm shift from conventional perception

Abstract: Apolipoprotein E (APOE) is a major protein component of peripheral and brain lipoprotein transport systems. APOE in peripheral circulation does not cross the blood brain barrier or blood cerebrospinal fluid barrier. As a result, peripheral APOE expression does not affect brain APOE levels and vice versa. Numerous epidemiological studies suggest a key role of peripherally expressed APOE in the development and progression of coronary heart disease while brain APOE has been associated with dementia and Alzheimer’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Interpretation of these traditional AD risk factors are complex. Several studies suggest a strong link between ApoE and overweight/obesity [ 82 ]. ApoE -/- mice accumulate less body fat content and possess smaller adipocytes compared to wild type C57BL/6 controls [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of these traditional AD risk factors are complex. Several studies suggest a strong link between ApoE and overweight/obesity [ 82 ]. ApoE -/- mice accumulate less body fat content and possess smaller adipocytes compared to wild type C57BL/6 controls [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another function of AGEs relevant to lipid metabolism is the inhibition of apolipoprotein E (ApoE) expression. ApoE, as a component of very low density lipoproteins (VLDLs), remnant lipoproteins, and high-density lipoproteins, contributes to lipoprotein internalization and degradation [ 47 , 48 ]. Using 3T3-L1 cells and mouse models, researchers observed that in hyperglycemic conditions, oxidative stress and the NF-κB pathway mediate ApoE abolishment.…”
Section: Influence Of the Rage Pathway On Adipose Tissue Activitymentioning
confidence: 99%
“…Briefly, APOE3 expressed in the brain inhibited oxidative phosphorylation in visceral WAT mitochondria, leading to increased body weight and obesity in response to a Western-type diet. In contrast, hepatic APOE3 expression (i.e., APOE3 presence only in the periphery) triggered increased thermogenesis in visceral WAT mitochondria, leading to a lean phenotype [ 39 ]. Yet, it is still unclear exactly how hepatically or cerebrally produced APOE affects WAT metabolism.…”
Section: High-density Lipoprotein and Adipose Tissue Metabolic Activitymentioning
confidence: 99%
“…Yet, it is still unclear exactly how hepatically or cerebrally produced APOE affects WAT metabolism. These findings constitute a major “paradigm shift” from the existing perception of Apoe when peripheral expression of APOE promotes obesity via receptor-mediated postprandial delivery of dietary lipids to WAT [ 39 ].…”
Section: High-density Lipoprotein and Adipose Tissue Metabolic Activitymentioning
confidence: 99%